Animal migration in the Anthropocene: threats and mitigation options - Cooke, Steven J; Piczak, Morgan L; Singh, Navinder J; Åkesson, Susanne; Ford, Adam T; Chowdhury, Shawan; Mitchell, Greg W; Norris, D Ryan; Hardesty-Moore, Molly; McCauley, Douglas; Hammerschlag, Neil; Tucker, Marlee A; et al. (Biological reviews of the Cambridge Philosophical Society, 2024)
Animal migration has fascinated scientists and the public alike for centuries, yet migratory animals are facing diverse threats that could lead to their demise. The Anthropocene is characterised by the reality that humans are the dominant force on Earth, having manifold negative effects on biodiversity and ecosystem function. Considerable research focus has been given to assessing anthropogenic impacts on the numerical abundance of species/populations, whereas relatively less attention has been devoted to animal migration. However, there are clear linkages, for example, where human-driven impacts on migration behaviour can lead to population/species declines or even extinction. Here, we explore anthropogenic threats to migratory animals (in all domains - aquatic, terrestrial, and aerial) using International Union for the Conservation of Nature (IUCN) Threat Taxonomy classifications. We reveal the diverse threats (e.g. human development, disease, invasive species, climate change, exploitation, pollution) that impact migratory wildlife in varied ways spanning taxa, life stages and type of impact (e.g. from direct mortality to changes in behaviour, health, and physiology). Notably, these threats often interact in complex and unpredictable ways to the detriment of wildlife, further complicating management. Fortunately, we are beginning to identify strategies for conserving and managing migratory animals in the Anthropocene. We provide a set of strategies that, if embraced, have the potential to ensure that migratory animals, and the important ecological functions sustained by migration, persist.
Keywords: Biodiversity; migrace zvířat; animal movement; Climate Change; Ecosystem; biodiversity; Animal Migration; biodiverzita; natural resources management; conservation; Conservation of Natural Resources; Animals; lidé; zachování přírodních zdrojů; Humans; wildlife biology; zvířata; lidské činnosti; klimatické změny; ekosystém; phenology; Human Activities